Reproductive-Triggered Sterol Competition Exacerbates Age-Related Intestinal Barrier Damage in Drosophila Females. - Yu, G.; Chen, K.; Yang, M.; Wu, Q. (Aging Cell, 2025)
The trade-off between reproduction and lifespan has been documented across a wide array of organisms, ranging from invertebrates to mammals. In malnourishing dietary conditions, inhibition of the reproductive processes generally extends the lifespan of females. However, the underlying mechanisms through which nutritional competition driven by reproduction accelerates aging remain poorly understood. Here, using female Drosophila melanogaster as a model, we show that among various dietary conditions lacking specific nutrients, only sterol deficiency significantly exacerbated both the incidence and severity of intestinal barrier deterioration during aging. Sterile mutation specifically ameliorated such damage in sterol-deprived diets, but failed to alleviate age-related intestinal barrier deterioration under other nutritional conditions. Additionally, we demonstrate that the lifespan extension and intestinal barrier amelioration, accompanied by a reproductive suppression effect, through the pharmacological inhibition of mTOR or Ras-Erk signaling using rapamycin or trametinib, were significantly modulated by cholesterol levels. Our study also identifies the morphological changes in excreta as a sensitive biomarker for early intestinal dysfunction. Collectively, these results suggest that the impairment of the intestinal barrier caused by reproductive-induced sterol competition constitutes a significant factor limiting female lifespan in nutritionally unbalanced diets. This work elucidates a salient aspect of the complex interplay between reproductive resource allocation and somatic maintenance, thereby enhancing our understanding of how diet impacts the aging process.